Do Racists Play Video Games? The Dialectic Relation of White Supremacists to Popular Culture (KULT_online, 2015)
Cultural critics C. Richard King and David J. Leonard shed light on the complex relation of white power and popular culture in the contemporary US. By analysing online discussion forums of white supremacists, the authors trace the dialectics of rejecting and re-appropriating popular culture commodities in fields as diverse as music, sports, and video games; furthermore, King and Leonard lay bare the at times thin red line between mainstream discourses around popular culture and white nationalist attitudes towards this phenomenon.